1991
DOI: 10.1104/pp.96.3.686
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod Control of Poplar Bark Storage Protein Accumulation

Abstract: Bark storage proteins (BSPs) accumulate in the inner bark parenchyma of many woody plants during autumn and winter. We investigated the effect of a short-day (SD) photoperiod on the accumulation of the 32-kilodalton bark storage protein of poplar (Populus deltoides Bart. ex Marsh.) under controlled environmental and natural growing conditions. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis and protein gel blot analysis revealed that 10 days of SD exposure (8 hours of light) resulted in a 20% increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 29 publications
(23 reference statements)
6
94
0
1
Order By: Relevance
“…7). This protein band corresponds in size to VSP previously characterized in poplar bark (Coleman et al, 1991;Langheinrich & Tischner, 1991). The comparison between stained SDS-PAGE gels from control and transgenic plants showed that the 32-kDa polypeptide accumulated in transgenic stems more quickly than in control plants (Fig.…”
Section: Tree Growth and Gs1 Content In Leafmentioning
confidence: 99%
“…7). This protein band corresponds in size to VSP previously characterized in poplar bark (Coleman et al, 1991;Langheinrich & Tischner, 1991). The comparison between stained SDS-PAGE gels from control and transgenic plants showed that the 32-kDa polypeptide accumulated in transgenic stems more quickly than in control plants (Fig.…”
Section: Tree Growth and Gs1 Content In Leafmentioning
confidence: 99%
“…Hybridizations were carried out in the same buffer overnight at 65°C. RNA blots were washed once in lx SSC and 0.1% SDS at room temperature for 20 (1). The library was screened with BSP antiserum resulting in one positive clone/ 1300 plaqueforming units.…”
Section: Protein Sequencingmentioning
confidence: 99%
“…Poplar BSP was partially purified as described previously (1). Approximately 1000 pmol of partially purified protein was further purified by SDS-PAGE and blotted to polyvinylidene difluoride membrane (Immobilon P, Millipore) as described by LeGendre and Matsudaira (12).…”
Section: Protein Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a variety of storage proteins have been detected in bark and other tissues of hardwoods and softwoods (Coleman et al, 1991;Wetzel et al, 1991;Harms and Sauter, 1992). These studies point to the diverse locations of VSP throughout the plant body and also illustrate the physiological and biochemical mechanisms that different tissues use to store nutrients.…”
mentioning
confidence: 99%